Atmospheric Hazards Case Studies in Modeling, Communication, and Societal Impacts - Coleman, Jill S. M. (IntechOpen, 2016)
Natural and environmental hazards research comprises a diverse set of subjects and methodologies and this book is no exception - offering the reader only a small glimpse into the physical and social processes that threaten human interests. Atmospheric Hazards-Case Studies in Modeling, Communication, and Societal Impacts explores atmospheric-based hazards through focused investigations ranging from a local to global perspective. Within this short compendium, the major scales of atmospheric motion are well represented with topics on microscale turbulent transport of pollutants, mesoscale events stemming from thunderstorm complexes, and synoptic scale extreme precipitation episodes. Chapters include discussions on modeling aspects for investigating hazards (pollution, regional climate models) and the forecasting and structure of high wind events (derechos), whereas others delve into hazard communication, preparedness, and social vulnerability issues (tornadoes, hurricanes, and lightning). Although the chapters are quite disparate upon first inspection, the topics are united through their interweaving of both the physical and societal mechanisms that create the atmospheric hazard and eventual disaster.